Analysis of Power Parameters of Combined Three-Direction Deformation of Parts with Flange - Aliieva, L.; Markov, O.; Aliiev, I.; Hrudkina, N. S.; Levchenko, V.; Malii, Kh. V.; Грудкіна, Н. С.; Малій, Х. В. (University of Belgrade, 2021)
The upper bound power method is used to simulate the process of combined radial-backward-forward extrusion of hollow parts of the «cup with flange and branch pieces» type from a continuous workpiece. The calculation scheme with autonomous deformation zones is used, which contains modules with an inclined boundary and the condition for the equality of powers acting on both sides of the intermediate hard zone is accepted. This made it possible to more accurately determine the power regime and the prevailing direction of the metal flow, which is necessary to assess the character of the forming of the part. The comparison of theoretical and experimental values of the deformation pressures and the flow velocities with each other, as well as with the results obtained by the finite element method shows the feasibility of using the obtained functions for technological calculations of power parameters and evaluating of part forming.
Keywords: extrusion; power mode; hollow stem part with flange; upper bound method; velocity field; kinematic module; finite element method